PKM Pasang Planel Surya Oven Biovina Untuk Perbaikan Bahan Baku: Penurunan Kadar Air dan Kontaminasi Kapang: PKM Installs Planel Solar Biovina Oven for Raw Material Repair: Moisture Content Reduction and Mold Contamination - Nainggolan, Nelson; Pandiangan, Dingse; Adinata, Harni Seven (Sam Ratulangi University, 2024)
Biovina MSME products received directions from BPOM to re-test products that will be registered with BPOM. It was only after Biovina repaired the raw materials used that were drier and only re-tested because the previous materials were too old so that the results did not meet the requirements (not standardized). Because of this situation, Inventors always help MSMEs in meeting their needs so that they can still be worthy of CPOTB. Assistance is carried out so that problems can be overcome. The purpose of this program is to improve the process of providing quality raw materials with BPOM standards with a good drying process. Good products from standardized raw materials by improving and offering new products in the form of capsules and dryers that are fast and feasible according to BPOM standards. The specific target and purpose of this assistance is the process of making a large Biovina dryer power source and the electricity often goes out so that the raw materials are not good. Through this assistance, electricity from solar power is made with a size of 2x1 meters so that it can reduce electricity expenditure every day so that drying and the quality of raw materials and products increase and improve. A stable power source certainly improves the drying and processing process according to BPOM standards and the form of products in capsules registered and certified at BPOM and ready to use which are marketed online or on the website. The implementation methods that will be applied to this program are counseling, training, mentoring and evaluation of the aspects that cause the problems of the SMEs. The outputs of this program include Biovina products in the form of capsules that have been packaged in bottles and boxes that have been registered with BPOM and the results of the activity are published through Sinta 5 accredited journals. Keywords: Solar Energy; Drying; Quality Improvement; Product; Biovina. ABSTRAK Produk UMKM Biovina mendapat arahan dari BPOM untuk menguji kembali produk yang akan didaftarkan di BPOM. Kedudian setelah Biovina memperbaiki bahan baku yang digunakan yang lebih kering dan baru diadakan kembali pengujian karena bahan sebelumnya sudah terlalu lama sehingga hasilnya tidak memenuhi syarat (tidak terstandar). Oleh karena keadaan tersebut Inventor yang selalu membantu UMKM dalam memenuhi kebutuhannya agar tetap bisa layak CPOTB. Pendampingan dilakukan agar permasalahan dapat diatasi. Tujuan program ini untuk meningkatkan proses penyediaan bahan baku yang bermutu standar BPOM dengan proses pengeringan yang baik. Produk yang baik dari bahan baku yang terstandar dengan memperbaiki serta menawarkan produk baru dalam bentuk kapsul dan alat pengering yang cepat dan layak terstandar BPOM. Target dan tujuan khusus pendampingan ini adalah proses pembuatan sumber listrik alat pengering Biovina yang besar dan listrik sering padam sehingga bahan baku kurang yang baik. Melalui pendampingan ini listrik dari tenaga surya dibuat dengan ukuran 2x1 meter sehingga bisa menurunkan pengeluaran listrik setiap hari sehingga pengeringan dan mutu bahan baku dan produk meningkat dan terjada. Sumber listrik yang stabil tentu meningkatkan proses pengeringan dan pengolahannya terstandar BPOM serta bentuk produk dalam kapsul diregistrasi dan tersertifikasi di BPOM dan siap pakai yang dipasarkan secara online atau website. Adapun metode pelaksanaan yang akan diterapkan pada program ini yaitu penyuluhan, pelatihan, pendampingan dan evaluasi terhadap aspek-aspek yang menyebabkan masalah UKM tersebut. Luaran dari program ini meliputi produk Biovina dalam bentuk kapsul yang sudah dikemas dalam Botol dan kotak sudah teregistrasi di BPOM dan hasil kegiatas dipublikasi lewat jurnal terakreditasi Sinta 5.